Determinants of Development Financing Flows From Brazil, Russia, India, and China to Low-Income Countries - Mwase, Nkunde (Washington, D.C. : International Monetary Fund, 2011)
BRICs development financing flows have increased significantly and are expected to become more prominent in the post-crisis era. We investigate the potential implications on the country-allocation of loan commitments and the degree of concessionality using a panel vector autoregression model and single equation dynamic panel estimation.We find that BRICs lend more to LICs with weaker institutions. Land-locked, resource-scarce LICs receive significantly less financing than other resource-rich LICs. The degree of concessionality is negatively correlated with the amount of loans and positively correlated with better institutional indicators suggesting that the higher the risks, the higher the required returns that BRICs expect.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet